Interpretation of the prohibition of torture: making sense of 'dignity' talk - Webster, Elaine (Human rights review, 2016)
The right not to be subjected to torture, cruel, inhuman or degrading treatment or punishment is invariably associated with ‘human dignity’. The idea of dignity plays some role in this right’s interpretation, although the content of the idea in this context, as in others, is unclear. Making sense of the dignity idea involves a number of challenges. These challenges give rise to the methodological-type question at the heart of this article: how should human rights lawyers go about articulating the content of ‘dignity’? The article proposes, and models, a methodological approach in response. Its core argument is that human rights law needs the vocabulary provided by theorizations of dignity but that these theorizations should be anchored in authoritative human rights jurisprudence. It argues that this approach can help make sense of the dignity idea in a way that facilitates a richer understanding of its influence on interpretation.